Pengaplikasian Olah Data Penginderaan Jauh, Pendekatan dan Permodelan Geologi dalam Kajian Bencana Likuifaksi di Wilayah Kabupaten Sigi, Provinsi Sulawesi Tengah - Sinatrya Diko Prayudi; Rino Dwi Hutama; Aska Zakiya; Thomas Triadi Putranto; Devina Trisnawati (Prosiding TAU SNARS-TEK Seminar Nasional Rekayasa dan Teknologi, 2019)
Liquefaction is a natural phenomenon on the earth surface of the earth that quite dangerous to deadly if occurs in area with high population density. The case of Sigi Regency which took place on 28 September 2018 as a domino effect of 7,4 magnitude earthquake with an epicenter distance of 80 km from Palu City or 90 km from Petobo area, Sigi Regency. The aftershock that occur propagate below the surface, condensing and mixing loose material that accumulates with ground water when reaches target area. Those disasters had been predicted since 2012 by a number of researchers opened society mind about after impact phenomena from a main disaster that followed. The main result of this research focused on giving simple explanation about how the liquefaction occur in timescale using combination of remote sensing, geoscience data, and 3D-modelling. Through the analyzing of Landsat 8 as main remote sensing data from different acquisition time, it was found that there were significant changes in land use appearance between before and after the disaster. The topography shown through Digital Elevation Model (DEM) data presented both 3D and cross section increase the potential indication for liquefaction material movement that tends to descend the slope, from east to west. The geological approach taken refers to the literature study related to regional condition of study area which includes lithology – sedimentology, and structural geology. The result of the regional geology study found the combination of unconsolidated rocks in form of alluvium (Qa) – Pakuli Formation (Qp) and interaction of Palu – Koro fault line as deriving factor of liquefaction. Another factor such hydrogeology and geotechnical aspect indicated to play a role as a sufficiently strong trigger factor for the disaster to occur. From some aspect above are further overlayed in simple geological 3D-modelling to explain the sequence of events that occur and the role of each factor in causing liquefaction in the case study area.